Patient and Physician Perceptions of Virtual Visits for Parkinson's Disease: A Qualitative Study - Mammen, Jennifer R; Elson, Molly J; Java, James J; Beck, Christopher A; Beran, Denise B; Biglan, Kevin M; Boyd, Cynthia M; Schmidt, Peter N; Simone, Richard; Willis, Allison W; Dorsey, E Ray (Telemedicine journal and e-health, 2018)
Background and Introduction: Delivering care through telemedicine directly into the patient's home is increasingly feasible, valuable, and beneficial. However, qualitative data on how patients' and physicians' perceive these virtual house calls are lacking. We conducted a qualitative analysis of perceptions of these visits for Parkinson's disease to (1) determine how patients and physicians perceive virtual visits and (2) identify components contributing to positive and negative perceptions. Qualitative survey data were collected from patients and physicians during a 12-month randomized controlled trial of virtual house calls for Parkinson's disease. Data from 149 cases were analyzed using case-based qualitative content analysis and quantitative sentiment analysis techniques. Positive and negative perceptions of virtual visits were driven by three themes: (1) personal benefits of the virtual visit, (2) perceived quality of care, and (3) perceived quality of interpersonal engagement. In general, participants who identified greater personal benefit, high quality of care, and good interpersonal engagement perceived visits positively. Technical problems with the software were commonly mentioned. The sentiment analysis for patients was strongly favorable (+2.5) and moderately favorable for physicians (+0.8). Physician scores were lowest (-0.3) for the ability to perform a detailed motor examination remotely. Patients and providers generally view telemedicine favorably, but individual experiences are dependent on technical issues. Satisfaction with and effectiveness of remote care will likely increase as common technical problems are resolved.